Knowledge, attitude and risky practices on schistosomiasis in Ethiopia: A scoping review - Getaneh Alemu; Endalkachew Nibret; Abaineh Munshea; Melaku Anegagrie; Arancha Amor (PLoS ONE, 2025)
Background Despite many years of intervention measures, schistosomiasis (SCH) remains a public health problem in Ethiopia. Health education and promotion enable community involvement and active participation in SCH control and prevention. Therefore, it is considered as one of the key strategies to prevent and control SCH in Ethiopia. However, comprehensive data on the knowledge, attitude and practice (KAP) of vulnerable populations towards the disease are lacking. Therefore, we reviewed the existing KAP studies in Ethiopia. Methods Studies conducted in Ethiopia and published between 2006 and 2023 were searched and reviewed from January to April 2024. Electronic literature searches were made in PubMed, Hinari, African Journal Online and Google Scholar using the keywords “Schistosomiasis, Schistosoma , Schistosoma mansoni , Schistosoma haematobium , Knowledge, Attitude, Practice, Perception, Belief, Ethiopia” by combining them with Boolean operators (AND, OR). The review was conducted according to the Arksey and O’Malley Framework for scoping reviews, and studies were selected based on the PRISMA guidelines. Thematic analysis was applied to summarize, synthesize and report results. Results Ten studies that recruited 4,763 participants were included in the present review. Knowledge gaps on the source of Schistosoma infection, transmission, morbidity, treatment, and prevention in Ethiopia were identified. Studies have found large differences in attitudes toward SCH in terms of the population at risk, the severity of the disease, and beliefs in the availability and success of its treatment and prevention. Furthermore, in most studies included in this review, the majority of participants had negative attitudes towards SCH. The majority of participants also engaged in risky water-related practices, which facilitated the ongoing transmission of SCH. KAP levels among community members, school-aged children, and mothers/caregivers of preschool-aged children showed no significant differences. Conclusions The results of this systematic review showed that the KAP level is inadequate despite health education platforms that have been established and implemented for many years. Therefore, we recommend strengthening the implementation of health education and continuous monitoring of SCH prevention and control activities.